A utilização dos materiais didáticos nas aulas de Matemática - Um estudo no 1o Ciclo - Dilaila Botas; Darlinda Moreira (Universidade do Minho, 2013)
The article presents a research whose main objective was to find out the most frequent pedagogic materials used in mathematics education in a Group of Elementary Schools in the Lisbon area and what was the educational vision underlying their use. Methodologically, it was followed a quantitative study with descriptive characteristics. The population involved in the study was the 53 elementary teachers that belong to the Group of Schools. The conclusions pointed out that teachers define pedagogic material as an object aimed at motivating the students, helping them in the construction of mathematical concepts. The textbook, the student's own body, as well as rules and abacus are the most frequent materials. Teachers considered didactical materials very important and stated that they often use them both to solve problems and to practice comprehensive procedures.